Factors influencing CPA practitioners of selected schools in choosing the academe sector - Abella, Clarisse Jewel P.; Anata, Ma. Angelica C.; Beduya, Lyrehs Evets J.; Buenaventura, Aira M.; Francisco, Kristine G.; Hilario, Roger Jr. E.; Nitario, David John C.; Vergara, Patrick John M. 4 0 16; 5
ABSTRACT: This quantitative research discussed and determined the Factors Influencing CPA Practitioners of Selected Schools in Choosing the Academe Sector. The accounting profession is mainly divided into four (4) sectors, namely: public accountancy, commerce and industry, academe/education, and government. The focus of the study was the academe/education sector as the researchers discovered that there has been a shortage of professors in its faculty. This has been proven based on various past studies. The researchers were able to to determine four (4) factors, namely intrinsic rewards, extrinsic rewards, path to advancement, and job manageability, that affects CPA practitioners choice in taking a career in teaching. This study included 124 respondents coming from five (5) different schools in Manila, 41.90% of respondents are full-time employees and 58.10% are part-time employees. The participating schools were FEU-Manila, LPU-Manila, NU-Manila, PSBA, and San Beda University. Through an online survey using Google Forms, the respondents were asked how much they value each factor and how much they are willing to take a career in teaching. Furthermore, the researchers analyzed the data gathered by using multiple statistical tools such as Analysis of Variance to answer SOP 3 of the study and Pearson-R Correlation to answer SOP 4 of the study. To quantify and interpret the result for SOPs 1 and 2, researchers applied the mean, weighted mean, and frequency and percentage distribution. The study indicates that there is a significant relationship between the four (4) factors and the willingness of CPA practitioners to take a career in teaching. The study concludes that respondents are willing to take the academic field as they highly value all factors identified. Job manageability is the factor that greatly influences CPA practitioners in pursuing to become a professor regardless of what type of employment they are in.
Research Paper: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2023
Keywords: 2 -- 0; 6; 20; 20; 2